Eksperimentasi Model Pembelajaran Kooperatif Tipe Tapps dan GI pada Kemampuan Pemecahan Masalah Matematika Ditinjau dari Tipe Kepribadian Peserta Didik SMP Se-Kabupaten Pacitan - Dwi Cahyani Nur Apriyani (Jurnal Penelitian Pendidikan, 2013)
This research is kind of quasi-experimental research by 3x4 factor design. The population of this research is all students of class VII at the States Junior High School (SMP Negeri) in Pacitan Regency of 2011/2012 academic year. The data collection was done using questionnaire, test, and documentation techniques. The problem solving ability is tested with essay test, while the personality type identified with a questionnaire. Data analysis using varians analysis (Anava) with different cells size. The conclusions of this research were: (1) GI and TAPPS provide better problem-solving ability than the conventional learning model on students in junior class VII Pacitan academic year 2011/2012. However, among students with GI learning models and TAPPS learning models, have the same problem-solving abilities, (2) students with artisan type or rational type has better problem solving ability better students with idealist or guardian type. However, both the students with artisan and rational type have the same problem-solving abilities. Learners with idealist and guardian types also have the same problem-solving ability, (3a) in the class using the GI and TAPPS learning model, problem-solving abilities of students with artisan or rational personality type is better when compared to problem-solving abilities of students with guardian or idealist personality type. Eventhough, in a class that uses conventional learning models, all groups of personality types have the same problem-solving ability, and (3b) for artisan or rational personality, GI and TAPPS provide better problem-solving ability than the conventional learning model. The inconclusion all learning models give the same problem solving abilities for idealist or guardian personality type.